Niosomal Gel: A Promising Approach for Enhanced Topical Drug Delivery - Bhoyar V. Vikram; Dr. Vikrant P. Wankhade; Dr. Shrikant D. Pande; Dr. Sandeep C. Atram; Dr. Nishan N. Bobade; Tanvi S. Kokate; Neha S. Ghogare (Asian Journal of Pharmaceutical Research and Development, 2025)
This review highlights the formulation and evaluation of niosomal gels as an advanced strategy for topical drug delivery. Niosomes, vesicular systems composed of non-ionic surfactants, were developed and optimized based on critical parameters such as particle size, entrapment efficiency, and formulation stability. These optimized vesicles were then incorporated into a suitable gel base for effective dermal application. The resulting niosomal gel was systematically evaluated for physicochemical properties including pH, viscosity, spreadability, and drug content uniformity. Ex vivo skin permeation studies revealed significantly enhanced drug penetration compared to conventional gel formulations, while in vivo assessments demonstrated improved therapeutic outcomes and prolonged anti-inflammatory effects. Overall, niosomal gel systems offer a promising, controlled, and targeted approach to enhance the efficacy and patient compliance in topical drug delivery.